Posterior approach to the rectum: Kraske via. Discussion of 4 cases - Pradines, Jorge; Carriquiry, Luis; Piacenza, Guillermo; Rodríguez, José (Cirugía del Uruguay, 1985)
The rear approach to the rectum, inítially proposed by Kraske, later on disesteemed in the benefit of Miles technique, has been reinstalled for the treatment of some benign lesions of the middle rectum.